Parsimony or Poor Luck: Concurrent Birt-Hogg- Dubé Syndrome and Sarcoidosis - Kuhn, Brooks Thomas; Teckchandani, Priyanka Heeru; Harper, Richart William (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
While sarcoidosis is notorious for myriad manifestations including cystic lung changes, we present a case with both Birt-Hogg-Dubé syndrome (BHD) and pulmonary sarcoidosis. BHD is a rare, autosomal dominant genetic disorder characterized by numerous thin-walled, irregular cysts, but lung function is typically normal otherwise. We present a case with confirmed BHD syndrome and concurrent granulomatous lung disease consistent with sarcoidosis.